Bone morphogenetic protein signaling pathway: an essential role in intestinal homeostasis and diseases: BMP pathway in intestinal homeostasis and diseases - Cogo, Emma; Guéraud, Françoise; Plaisancie, Pascale (Cellular and Molecular Biology, 2025)
The bone morphogenetic protein (BMP) signaling pathway is a fundamental regulator of intestinal homeostasis, orchestrating the delicate balance between stem cell proliferation and epithelial differentiation along the crypt-villus axis. In opposition to the Wnt signaling pathway, BMP signaling promotes epithelial maturation and inhibits excessive stem cell expansion, thereby ensuring proper renewal and functional integrity of the intestinal epithelium. Both epithelial and mesenchymal cell populations actively contribute to BMP signaling; mesenchymal cells serve as a primary source of BMP ligands and antagonists, while epithelial cells predominantly express BMP receptors and downstream effectors. This dynamic epithelial-mesenchymal dialogue establishes and maintains the intestinal stem cell niche and structural organization of the crypts. Dysregulation of BMP signaling has been increasingly implicated in the pathogenesis of inflammatory bowel diseases (IBD) such as Crohn’s disease and ulcerative colitis, as well as in colorectal cancer (CRC). In inflammatory conditions, modulation of BMP ligands and antagonists influences epithelial regeneration and immune responses, highlighting their potential anti-inflammatory and anti-fibrotic roles. Conversely, in colorectal carcinogenesis, alterations in BMP pathway components—including mutations in BMP receptors and Smad effectors, alongside aberrant expression of BMP antagonists like Gremlin-1—disrupt the balance of intestinal homeostasis, promoting tumor initiation, progression, and metastatic potential via both canonical and non-canonical signaling mechanisms. This review comprehensively summarizes the current understanding of BMP signaling in intestinal physiology and pathology, emphasizing the critical interplay between epithelial and mesenchymal compartments, and the impact of the genetic context and pathway modulators. Further elucidation of BMP pathway dynamics promises novel therapeutic strategies for intestinal diseases through targeted modulation of this pivotal signaling cascade.